THE EFFECT OF PERCEIVED JUSTICE TOWARD RECOVERY SATISFACTION: A STUDY ON CITILINK AIRLINE CUSTOMERS - FAJ LILLAH, ILHAM FIJAJAN (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research aims to examining the Effect of Perceived Justice Toward Recovery Satisfaction. There are three independent variables included in the distributive justice, interactional justice, and procedural justice. The three independent variables were investigated to see the impact on customer satisfaction after service recovery. This research conducted in Malang City. The questionnaire has been distributed as much as 300 to all Citilink airline customers that have experienced in service failure and service recovery in Indonesia. The sampling technique used is purposive technique sampling and the research instruments were tested using the validity test, reliability test, and classical assumption test. The hypotheses used partial (T-test). Result of the data analysis from multiple regression showed that the three independent variables give significant effect on recovery satisfaction. The results of this research can be applied in a marketing strategy for theÂ company and interested parties to maintain and maximize distributive justice, interactional justice, and procedural justice to get a positive effect to recovery satisfaction.Â Key Words: Perceived Justice, Distributive Justice, Interactional Justice, Procedural Jusitce, and Recovery Satisfaction